Effects of Drought Manipulation on Soil Nitrogen Cycling: A Meta‐Analysis. Issue 12 (23rd December 2017) - Homyak, Peter M.; Allison, Steven D.; Huxman, Travis E.; Goulden, Michael L.; Treseder, Kathleen K.
Abstract: Many regions on Earth are expected to become drier with climate change, which may impact nitrogen (N) cycling rates and availability. We used a meta‐analytical approach on the results of field experiments that reduced precipitation and measured N supply (i.e., indices of N mineralization), soil microbial biomass, inorganic N pools (ammonium (NH4 + ) and nitrate (NO3 − )), and nitrous oxide (N2 O) emissions. We hypothesized that N supply and N2 O emissions would be relatively insensitive to precipitation reduction and that reducing precipitation would increase extractable NH4 + and NO3 − concentrations because microbial processes continue, whereas plant N uptake diminishes with drought. In support of this hypothesis, extractable NH4 + increased by 25% overall with precipitation reduction; NH4 + also increased significantly with increasing magnitude of precipitation reduction. In contrast, N supply and extractable NO3 − did not change and N2 O emissions decreased with reduced precipitation. Across studies microbial biomass appeared unchanged, yet from the diversity of studies, it was clear that proportionally smaller precipitation reductions increased microbial biomass, whereas larger proportional reductions in rainfall reduced microbial biomass; there was a positive intercept ( P = 0.005) and a significant negative slope ( P = 0.0002) for the regression of microbial biomass versus % precipitation reduction (LnR = −0.009 × (% precipitation reduction) + 0.4021). Our analyses imply that relative to other N variables, N supply is less sensitive to reduced precipitation, whereas processes producing N2 O decline. Drought intensity and duration, through sustained N supply, may control how much N becomes vulnerable to loss via hydrologic and gaseous pathways upon rewetting dry soils. Plain Language Summary: Many regions on Earth are expected to become drier with climate change, which may impact nitrogen (N) cycling rates and availability. We summarized the results of experiments reducing precipitation input to ecosystems and measured the effects on N cycling. Because microbes are sensitive to changes in moisture and their activity decreases as soils dry, reducing precipitation could lower N cycling rates. However, we found that reducing precipitation did not shut down the supply of mineral N to ecosystems and that microbial biomass actually increased with relatively minor rainfall reduction but that microbial biomass decreased upon exposure to further water limitation. Our results expand on early laboratory studies evaluating N dynamics in dry soils. While it is clear that microbial N transformations decrease in dry soils incubated in the laboratory, we show that, under field conditions, some N cycling processes are less sensitive to precipitation reduction. Nonrainfall water inputs, such as the movement of atmospheric water vapor into soil, can stimulate drought‐tolerant microbial processes in the field and may maintain active microbial N processing despite low water content when soils are measured in bulk. Sustained N processing during drought could result in greater ecosystem N losses during subsequent wetting events. Key Points: A meta‐analytical approach was used on 37 studies that reduced precipitation The supply of mineral N did not decrease under drought treatment; extractable NH4 + increased 25% Microbial biomass and N2 O emissions declined, and NH4 + increased with increasing drought intensity